Lifestyle Related Behavioral Changes Owing to the Global Pandemic among COVID-19 Positive Physicians Serving in a COVID Dedicated Tertiary Care Hospital (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: The COVID-19 pandemic continues to pose significant challenges and has had a global effect on people’s lifestyle. The impact of measures taken to contain COVID-19 on lifestyle related behavior is undefined among physicians with COVID-19 positive serving in a corona dedicated health center.Objective: The current study was undertaken to assess the impact of COVID-19 on life style related behaviors among physicians with COVID-19 including all human sciences related to lifestyle, dietary habits physical activity and behavioral studies.Methods: The study is a descriptive type of cross-sectional web-based survey. The survey was conducted from March to May, 2021 among 61 COVID-19 infected physicians working at Mugda Medical College Hospital through a validated semi-structured questionnaire incorporated with GAD-7 scale using Google online survey platform. The sample was selected purposively and collected data were analyzed by SPSS-21 version. The P-value was two sided and values